CD200-CD200R1 interaction contributes to neuroprotective effects of anandamide on experimentally induced inflammation. - Hernangómez, M; Mestre, L; Correa, F; Loría, F; Mecha, M; Iñigo, P; Docagne, F; Williams, R; Borrell, J; Guaza, C (2012)
The endocannabinoid anandamide (AEA) is released by macrophages and microglia on pathological neuroinflammatory conditions such as multiple sclerosis (MS). CD200 is a membrane glycoprotein expressed in neurons that suppresses immune activity via its receptor (CD200R) mainly located in macrophages/microglia. CD200-CD200R interactions contribute to the brain immune privileged status. In this study, we show that AEA protects neurons from microglia-induced neurotoxicity via CD200-CD200R interaction. AEA increases the expression of CD200R1 in LPS/IFN-γ activated microglia through the activation of CB(2) receptors. The neuroprotective effect of AEA disappears when microglial cells derive from CD200R1(-/-) mice. We also show that engagement of CD200R1 by CD200Fc decreased the production of the proinflammatory cytokines IL-1β and IL-6, but increased IL-10 in activated microglia. In the chronic phases of Theiler's virus-induced demyelinating disease (TMEV-IDD) the expression of CD200 and CD200R1 was reduced in the spinal cord. AEA-treated animals up-regulated the expression of CD200 and CD200R1, restoring levels found in sham animals together with increased expression of IL-10 and reduced expression of IL-1β and IL-6. Treated animals also improved their motor behavior. Because AEA up-regulated the expression of CD200R1 in microglia, but failed to enhance CD200 in neurons we suggest that AEA-induced up-regulation of CD200 in TMEV-IDD is likely due to IL-10 as this cytokine increases CD200 in neurons. Our findings provide a new mechanism of action of AEA to limit immune response in the inflamed brain.